Dynamics of Gender Equality for Women in the Middle East: An Examination of Cultural Psychology and Islamic Jurisprudence - Jihaddin, Muhammad Hazikri; Nurwahidin; Hannase, Mulawarman; Muttaqin, Mohammad Izdiyan (Formosa Journal of Sustainable Research, 2024)
Society frequently perceives women as vulnerable and subordinate to regulations. In the traditional environment of Saudi Arabia, women experience restricted mobility and social engagement. The notable distinction from other nations is in the enforcement of regulations and cultural practices that discriminate based on gender and uphold male guardianship laws. Consequently, the cultural environment is perceived as hostile towards women. Furthermore, Saudi Arabia's global reputation on gender equality is very negative. Saudi Arabia seems to have misunderstood perspectives on women's human rights in its policy-making. The interpretation of the Koran and hadith must be scrutinized if it is unjust to women. Saudi ladies are beginning to perceive a promising future for him. Crown Prince Muhammad exerted significant efforts to implement substantial reforms. Diverse reforms, including gender equality, were implemented to portray a moderate and amicable Islam. Saudi women have transformed their societal presence, beginning to embrace their rights and responsibilities in the public domain